(3YbhO GdeSJbHdjGJ ,GdNjGQGJ, GdeHGOdGJs - (3MGce eMSf(B, (3GdQHjYjs; (3ejKGb gGJa GdaJdGhj(B;(3MjOQ NVjQ LhGf(B, s ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2011)
1)(3GdeTJbGJ(B: (3eaghe GdYbhO GdeSJbHdjI h WHjYJgG , GdJMhW , GdGSYGQ GdMGVQI h GdeSJbHdjI h feGPL GdJSYjQ , (B2) (3GdeTJbGJ GdeGdjI `` YbhO GdNjGQGJ(B: (3YbhO GdNjGQGJ h CfhGYgG , GdeNGWQI h GdJMhW , GdeTJbGJ GdeGdjI `` YbhO GdeHGOdGJ (B: (3GdeVJbGJ GdeGdjI , YbhO GdeHGOdGJ , GdeNGWQI h GdJMhW (B.s
(3eQGLY U(B.481s
Keywords: (3GdYbhOs; (3GdeGdjIs